Neutron emission during a nanosecond discharge in deuterium in a nonuniform electric field; Technical Physics; Vol. 57, iss. 1 - Lomaev M. I.; Nechaev B. A.; Padalko V. N.; Kuznetsov S. I. Sergey Ivanovich; Sorokin D. A.; Tarasenko V. F.; Yalovets A. P. (2012, 2012)
Neutron emission during a nanosecond deuterium discharge formed at the nonuniform electric field is investigated. A stable neutron yield is observed when the cathode is made of metallic plates covered by a layer of deuterated zirconium and the anode is made of stainless steel in the form of a tube. It is shown that, when the deuterium pressure equals several Torr, neutrons are emitted from both deuterated and deuterium-free cathodes. The influence of the anode design on the neutron yield is studied.